Strengthening Faith for Teacher Tadika Al-Fikh Orchard Malaysia - Hasanuddin Hasanuddin; Rizka Harfiani (Maslahah: Jurnal Pengabdian Masyarakat, 2023)
This article is the output of international community service activities. The aim of this activity is to strengthen the faith of teachers at Tadika Al-Fikh Orchard Malaysia. The service method used is Participatory Action Research (PAR) with a cycle of work steps including the stages to know, to understand, to plan, to act, and to change. The work matrix includes preparation activities, implementation of training activities, and evaluation of the achievements of the service program. The service partner involved is the owner of Tadika Al-Fikh Orchard which has 40 Tadika branches spread throughout Malaysia. The result of this service is an increase in teacher Tadika Al-Fikh Orchard's faith, which includes how to organize/maintain faith, understanding the function and benefits of faith in life, as well as how to shape the character/personality of believers.